(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
Is presented from a theoretical perspective and a theoretical approach to documentary Mathematics Education from the social critical theory of Adorno (1969) and Giroux (1989), the contributions of a philosophy of Critical Mathematics Education Skovsmose (1999) and have used some educators venezuelans. A review of the contributions has been made in mathematics education and its relationship with the critics. It outlines some venezuelans work of mathematics educators who have tried to link this relationship through teaching practice to in order to establish links between theory and practice that contributes to the mathematical literacy purpose of this education.